2021
DOI: 10.3389/fbioe.2021.645039
|View full text |Cite
|
Sign up to set email alerts
|

Is Extracellular Vesicle-Based Therapy the Next Answer for Cartilage Regeneration?

Abstract: “Extracellular vesicles” (EVs) is a term gathering biological particles released from cells that act as messengers for cell-to-cell communication. Like cells, EVs have a membrane with a lipid bilayer, but unlike these latter, they have no nucleus and consequently cannot replicate. Several EV subtypes (e.g., exosomes, microvesicles) are described in the literature. However, the remaining lack of consensus on their specific markers prevents sometimes the full knowledge of their biogenesis pathway, causing the au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 116 publications
(143 reference statements)
0
18
0
Order By: Relevance
“…The MSC secretome is composed of a wide variety of molecules. Nevertheless, since it has already been demonstrated that EVs derived from MSCs were able to enhance chondrocyte proliferation, delay experimentally induced OA, and even repair cartilage [ 6 ], we hypothesized that equine MSC-derived EVs could participate in the effect we observed with eACs. The size and concentration of nanoparticles included in MSC-CM were assessed by nanoparticle tracking analysis (NTA).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…The MSC secretome is composed of a wide variety of molecules. Nevertheless, since it has already been demonstrated that EVs derived from MSCs were able to enhance chondrocyte proliferation, delay experimentally induced OA, and even repair cartilage [ 6 ], we hypothesized that equine MSC-derived EVs could participate in the effect we observed with eACs. The size and concentration of nanoparticles included in MSC-CM were assessed by nanoparticle tracking analysis (NTA).…”
Section: Resultsmentioning
confidence: 96%
“…A future study of the MSC-CM vesiculome, comprising EVs secreted by MSCs, could confirm our hypothesis. Indeed, several works in small mammal models have demonstrated that EVs derived from multipotent stem cells were able to enhance chondrocyte proliferation, delay experimentally induced OA, and even restore cartilage [ 6 ]. Additionally, EVs can have an equivalent or even a superior effect than the cell type they derive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, tissue regeneration relies on healing factors carried by EVs to generate a trophic microenvironment suitable for diseases. EVs can be untouched and used as therapeutic agents in their regular or natural state after isolation from biological samples or conditioned medium in standard cell culture conditions [ 62 ]. There is still a need for a consensus concerning EV isolation methods and EV characterization/designation remains.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles (EVs), which are nano- to micro-sized lipid bilayer membrane particles secreted by host cells, play critical roles in novel intercellular communication mechanisms, mediating the transduction of functional molecules with physiological activity, such as microRNAs, mRNAs, proteins, and lipids ( Figure 1 ) [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ,…”
Section: Introductionmentioning
confidence: 99%